(untitled) (San Diego, 1994)
The book provides a comprehensive and authoritative source of scientifically based information on a major laboratory animal species. The text emphasizes the normal biology as well as diseases of the European (domestic) rabbit, Orytolagus cuniculus, especially the New Zealand White breed, with occasional reference to other rabbit species (Sylvilagus sp.) and hares (Lepus sp.). New topics have been added to this second edition in response to changing trends in biomedical research and product testing
Keywords: Rabbits,Rabbits as laboratory animals,Rabbits; Diseases